Interação entre metabolismo e reprodução em ruminantes: efeitos da irisina e da restrição energética sobre a sinalização do interfeon tau - Silva, Ana Paula da (2025)
Reproduction in ruminants is a process highly dependent on metabolic balance, especially during early pregnancy, a critical period for maternal recognition of pregnancy (MRP). Nutritional and metabolic factors affect not only embryonic development but also the endocrine and paracrine signaling required for the maintenance of the corpus luteum (CL) and progesterone production. This study investigated the interaction between metabolism and reproduction in ruminants, focusing on the effects of irisin and negative energy balance (NEB) on interferon-tau (IFNT) signaling during early pregnancy. The first study employed an experimental sheep model to evaluate the consequences of NEB induction during the first (FW) or second week (SW) of pregnancy through feed restriction. Metabolic parameters (glucose and BHB), embryo recovery, progesterone concentration, and gene expression related to IFNT signaling (ISG15, MX1, MX2) and irisin (FNDC5, ITGB1, ITGAV) in the uterus and CL were assessed. Despite the induction of hypoglycemia and increased BHB levels, NEB did not impair conceptus recovery but modulated the expression of ISGs and steroidogenesis-related genes, suggesting uterine and luteal adaptations in response to the metabolic challenge. The second study was conducted in vitro using bovine luteal cells to investigate the role of irisin in IFNT-mediated signaling. The results showed that irisin enhanced IFNT-induced ISG expression (MX1, MX2) without affecting cell viability or the expression of steroidogenic genes. Together, the data indicate that both metabolic status and irisin modulation influence IFNT signaling in reproductive tissues, which may affect maternal recognition of pregnancy and maintenance of luteal function. These findings contribute to the understanding of integrative pathways between metabolism and reproduction, with relevant implications for reproductive efficiency in ruminants, especially under conditions of energy stress.